Efficiency Analysis of Production Management System - Oláh, Judit; Erdei, Edina; Popp, József (International Journal of Engineering and Management Sciences, 2017)
Due to the continuously evolving technology, even more escalating market competition has emerged between the companies. This competition is not only about the logistics related processes, it also appears to be significant for the production since the manufacturing companies form the center of global sale streams and without them the items found in logistical processes cannot be created. The role of production’s optimization and efficiency in the supply chain continuously grows since this is the part where a company’s most cost is produced. Our research objective was the examination of a company that applies various manufacturing, assembly technologies, and the used tools and softwares for this purpose were the SAP Business One ERP system and it’s add-on, called PPS One, the latter originated in Switzerland. We used these softwares to provide solutions to companies, especially to those that are dealing with manufacturing and production, for the optimization of their workflows, operations, supervising and controlling of their material. We also monitored from production technology’s elements the capacity planning, production orders, schedules, production tracking and cost accounting. We have made proposals during the analysis that might improve the company’s strategy, competitiveness and increase it’s efficiency in business, and at the same time they can facilitate the company’s pricing and inventory management activities.